Oxford reading tree : level 3 : more songbirds phonics : where is the snail? - Donaldson, Julia ([S.l.] : Oxford University Press, 2012)
Written by award-winning author Julia Donaldson, Songbirds Phonics are highly decodable, beautifully illustrated real stories. In Where is the Snail?, all the animals are busy, but the snail is hiding. The Level 3 More Songbirds phonics books revise all phonics previously covered in Songbirds Levels 1+, 2 and 3, and focus on matching a long vowel sound to one common letter pattern: for example, 'ee' as in 'three,' 'ie' as in 'tie' and 'oa' as in 'boat.' The invaluable inside cover notes enable parents/carers and teaching assistants to support children's word recognition and comprehension. Also available: * More Songbirds Level 3 Pack of 6 * More Songbirds Level 3 Class Pack of 36 * Level 3-4 eSongbirds Phonics CD-ROM, featuring e-versions of much-loved Songbirds stories for your interactive whiteboard, with audio activities and animations for consolidation and reinforcement.